Action for Increasing Diversity, Market Access, and Capacity in Oncology Registration Trials—Is Africa the Answer? Report From a Satellite Session of the Accelerating Anti-Cancer Agent Development and Validation Workshop. (17th June 2022) - Kizub, Darya; Manner, Cathyryne K.; Graef, Katy; Abubakar, Bello; Orem, Jackson; Odedina, Folakemi; Adeyeye, Mojisola Christianah; Nakigudde, Gertrude; Ayalew, Kassa; Kalidas, Chitkala; Lyerly, Herbert Kim; Norman, Thea; et al.
Abstract : Patients of African ancestry are not well-represented in cancer clinical trials despite bearing a disproportionate share of mortality both in United States and Africa. We describe key stakeholder perspectives and priorities related to bringing early-stage cancer clinical trials to Africa and outline essential action steps. Increasing Diversity, Market Access, and Capacity in Oncology Registration Trials—Is Africa the Answer? satellite session was organized at 2021 Accelerating Anti-Cancer Agent Development and Validation Workshop. Panelists included representatives of African Organization for Research and Training in Cancer, Uganda Cancer Institute, Uganda Women's Cancer Support Organization, BIO Ventures for Global Health, Bill & Melinda Gates Foundation, the US Food and Drug Administration, Nigeria's National Agency for Food and Drug Administration and Control, Bayer, and Genentech, with moderators from ASCO and American Cancer Society. Key discussion themes and resulting action steps were agreed upon by all participants. Panelists agreed that increasing diversity in cancer clinical trials by including African patients is key to ensuring novel drugs are safe and effective across populations. They underscored the importance of equity in clinical trial access for patients in Africa. Panelists discussed their values related to access and barriers to opening clinical trials in Africa and described innovative solutions from their work aimed at overcoming these obstacles. Multisectoral collaboration efforts that allow leveraging of limited resources and result in sustainable capacity building and mutually beneficial long-term partnerships were discussed as key to outlined action steps. The panel discussion resulted in valuable insights about key stakeholder values and priorities related to bringing early-stage clinical trials to Africa, as well as specific actions for each stakeholder group.